An object-oriented approach to education policy research: Deepening the analysis through an activity-theoretical and critical discourse analytic framework. (June 2017) - O'Connell, Catherine
Abstract: This paper responds to current conceptual interest in the policy object as a unit of analysis in education policy research. The theoretical perspectives of activity systems theory and critical discourse analysis are combined in a transdisciplinary framework to provide a fine- grained analysis of policy deliberation and a broader methodological apparatus with which to study discourse and activity. The value of this framework is illustrated through analysis of a policy-oriented text produced by a UK higher education mission group (the University Alliance) in the period preceding the UK general election in 2015. The analysis demonstrates how artefacts are deployed to mediate the policy object and illuminates how the group is claiming space in the policy sphere to challenge traditional constructions of research excellence which deprivilege this group. The emancipatory contribution of this form of strategic critique for policy communities is discussed. Highlights: A method for policy research which combines activity systems theory and critical discourse analysis Highlights how discourse and artefacts mediate policy object Illustrated through empirical example of UK higher education research funding policy deliberation